EFEKTIVITAS PENERAPAN CUSTOMER DUE DILLIGENCE PADA NASABAH BPR DALAM PENCEGAHAN PENCUCIAN UANG DI BATAM - Leslyn Kho; Tantimin Tantimin (LPPM Universitas Ekasakti Padang, 2022)
Banks are financial institutions that are quite needed by the community. Banks are characterized as insufficient domestic resources of domestic enterprises, low degree of structural transformation, inefficient government support, lack of policies to stimulate investors, imperfect legislative framework, high credit risk, associated with insufficient solvency of enterprises, underdevelopment of innovation and investment infrastructure. With the ease of facilities provided by banks, including the confidentiality of transactions, it is not surprising that many experienced actors use banking as a medium for money laundering. Even so, banks also have ways to prevent these criminal acts, one of which is through Cuctomer Due Dilligence (hereinafter abbreviated as CDD). This research method is carried out using empirical research methods with the research location being BPR in Batam. The results showed that at BPR Batam, CDD was carried out by updating data every 1 (one) year for customers with low to moderate risk. Meanwhile for high risk customers, CDD is conducted every 6 (six) months. The application of CDD at BPR Batam has proven to be effective in preventing money laundering practices. Regular updates allow banks to monitor each customer and their transactions. The effectiveness of the implementation of CDD is proven because there has never been any money laundering practice committed by customers at BPR Batam.